Human Capital Development and Organizational Survival: A Theoretical Review (International Journal of Management and Sustainability, 2018)
Effective human capital development is a major prerequisite to equip employees to acquire relevant new ideas, competencies and adapt to a changing market, and effectively drive organizational competitive advantage in order to achieve the survival goals. This paper theoretically examines the relationship between human capital development and organizational survival. It notes that human capital development is essential to equip the employees towards taking the organization to its expected destination. The paper concludes that by developing employee’s human capital, an organization improves her performance, productivity and innovative abilities which are essential for survival. In addition, human capital developments tend to turn human resources into a more tangible assets, as well as help match up the employees to strategic organization needs. It is recommended that organizations should invest in the various aspect of human capital development as it helps firms to attain greater performance and to remain competitive for their long-term survival. Business firms should cultivate high human capital development practices as human capital development drives employee’s loyalty, commitment and a sense of employee’s feeling of obligation toward the organization. Additionally, organizations should make human capital development an important aspect of their corporate strategic plan to upgrade their employees skills, enhance their conceptual knowledge, and broadens their understanding of the organizations total business objectives and values.